2012
DOI: 10.1021/je3008155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foam Boosters on the Micellization and Adsorption of Sodium Dodecyl Sulfate

Abstract: The interactions between the anionic surfactant sodium dodecyl sulfate and various foam boosters such as cocodiethanolamide, cocoamidopropylbetaine, and monoethoxylated cocomonoethanolamide are investigated. Interfacial interactions between sodium dodecyl sulfate and foam boosters were assessed by the surface tension method. An increase in the mole fraction of foam boosters reduced the critical micelle concentration (CMC) of anionic surfactant. The strength of interaction for micellization (βM) and adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The system which contained CAPB in association with SDS but not in enough concentration that it would allow formation of micelles too enhanced hydrate formation kinetics as compared to pure water, but the kinetics was largely the same when compared to the 1 wt % SDS system. There was a slight increase in the initial kinetics which may be down to the fact that the addition of CAPB lowers the surface tension of the system, allowing greater diffusivity of the gas initially . The 1 wt % CAPB system too showed kinetics akin to that for the 1 wt % SDS system with a considerable enhancement in the same when compared to pure water.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The system which contained CAPB in association with SDS but not in enough concentration that it would allow formation of micelles too enhanced hydrate formation kinetics as compared to pure water, but the kinetics was largely the same when compared to the 1 wt % SDS system. There was a slight increase in the initial kinetics which may be down to the fact that the addition of CAPB lowers the surface tension of the system, allowing greater diffusivity of the gas initially . The 1 wt % CAPB system too showed kinetics akin to that for the 1 wt % SDS system with a considerable enhancement in the same when compared to pure water.…”
Section: Resultsmentioning
confidence: 95%
“…There was a slight increase in the initial kinetics which may be down to the fact that the addition of CAPB lowers the surface tension of the system, allowing greater diffusivity of the gas initially. 29 The 1 wt % CAPB system too showed kinetics akin to that for the 1 wt % SDS system with a considerable enhancement in the same when compared to pure water. Thus, to sum up, when using pure methane as the hydrate forming gas, maximum enhancement in growth kinetics was observed with the 0.5 wt % SDS + 0.5 wt % CAPB system with the other three systems following close behind (the kinetics obtained for the latter three systems being too close to each other to confidently place them in an order).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, widely used anionic surfactant such as SDS and SDBS are efficient promoters for methane hydrate formation but their use for gas storage applications is not much feasible due to foam generation during degassing. Foam produced by SDS stays around for a long time due to its weak surface tension and high film strength because of its long alkyl chain . Heterogeneous promoters such as amphiphilic polymer-coated carbon nanotubes, grafting of nano-Ag particles on SO 3 – -coated nanopolymers, SO 3 – -coated graphene oxide nanosheets, and SO 3 – -coated nanopromoters help to alleviate foam formation by reducing the kinetics of hydrate formation. Bhattacharjee et al studied the antifoaming ability of silicon-based surfactants combined with SDS for methane hydrate formation and observed that the silicon-based surfactant not only exhibits excellent antifoaming characteristics but also enhances kinetics of methane hydrate formation.…”
Section: Gas Storage Capacitymentioning
confidence: 99%
“…的电性斥力, 增大界面吸附量, 提高界面活性的效果十 分显著 [9~11] . 也有报道表明两性表面活性剂与离子型表 面活性剂在混合胶束化和表面吸附中也存在复配协同 作用 [12,13] . 比如两性表面活性剂甜菜碱和离子型表面活 性剂十二烷基硫酸钠 SDS 混合体系的复配增效作用在 研究和应用中得到了证实 [14~16] .…”
unclassified